Retrograde Induction of phyB Orchestrates Ethylene-Auxin Hierarchy to Regulate Growth. Issue 3 (19th May 2020) - Jiang, Jishan; Xiao, Yanmei; Chen, Hao; Hu, Wei; Zeng, Liping; Ke, Haiyan; Ditengou, Franck A.; Devisetty, Upendra; Palme, Klaus; Maloof, Julin; Dehesh, Katayoon
Abstract : The plastidial retrograde metabolite MEcPP orchestrates coordination of the light and hormonal signaling cascade by inducing phytochrome B abundance and modulating auxin and ethylene levels. Abstract: Exquisitely regulated plastid-to-nucleus communication by retrograde signaling pathways is essential for fine-tuning of responses to the prevailing environmental conditions. The plastidial retrograde signaling metabolite methylerythritol cyclodiphosphate (MEcPP) has emerged as a stress signal transduced into a diverse ensemble of response outputs. Here, we demonstrate enhanced phytochrome B protein abundance in red light-grown MEcPP-accumulating ceh1 mutant Arabidopsis ( Arabidopsis thaliana ) plants relative to wild-type seedlings. We further establish MEcPP-mediated coordination of phytochrome B with auxin and ethylene signaling pathways and uncover differential hypocotyl growth of red light-grown seedlings in response to these phytohormones. Genetic and pharmacological interference with ethylene and auxin pathways outlines the hierarchy of responses, placing ethylene epistatic to the auxin signaling pathway. Collectively, our findings establish a key role of a plastidial retrograde metabolite in orchestrating the transduction of a repertoire of signaling cascades. This work positions plastids at the zenith of relaying information coordinating external signals and internal regulatory circuitry to secure organismal integrity.